2015
DOI: 10.1016/j.ebiom.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cyclic Adenosine Monophosphate (cAMP)-response Element-binding Protein (CREB)-binding Protein (CBP)/β-Catenin Reduces Liver Fibrosis in Mice

Abstract: Wnt/β-catenin is involved in every aspect of embryonic development and in the pathogenesis of many human diseases, and is also implicated in organ fibrosis. However, the role of β-catenin-mediated signaling on liver fibrosis remains unclear. To explore this issue, the effects of PRI-724, a selective inhibitor of the cAMP-response element-binding protein-binding protein (CBP)/β-catenin interaction, on liver fibrosis were examined using carbon tetrachloride (CCl4)- or bile duct ligation (BDL)-induced mouse liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 48 publications
1
85
0
Order By: Relevance
“…We had previously reported that PRI‐724, a selective inhibitor of the CBP/β‐catenin interaction, attenuates CCl 4 or BDL‐induced liver fibrosis . Similarly, PRI‐724 treatment reduced the liver fibrosis induced by an HFD plus GalN despite steatosis induction (http://onlinelibrary.wiley.com/doi/10.1002/hep4.1158/full).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We had previously reported that PRI‐724, a selective inhibitor of the CBP/β‐catenin interaction, attenuates CCl 4 or BDL‐induced liver fibrosis . Similarly, PRI‐724 treatment reduced the liver fibrosis induced by an HFD plus GalN despite steatosis induction (http://onlinelibrary.wiley.com/doi/10.1002/hep4.1158/full).…”
Section: Resultsmentioning
confidence: 99%
“…Liver macrophages contribute to liver fibrosis; depletion of liver macrophages suppresses liver fibrosis following BDL and decreases myofibroblasts in a liver tumor . Moreover, inhibition of CBP/β‐catenin promotes liver fibrosis resolution by macrophages . Although macrophages contribute to NASH development, the role of CBP/β‐catenin in liver macrophages during liver fibrosis in NASH is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, HSC-derived delta-like homolog 1 (DLK1) activates HSCs via epigenetic PPARγ repression and promote liver regeneration [152]. A selective inhibitor of the cAMP-response element-binding protein (CBP)/β-catenin interaction, PRI-724, inhibits HSC activation and reduces liver fibrosis in mice [153]. In contrast, β-catenin-dependent canonical Wnt activation is required to maintain quiescent state of HSCs in vitro [154].…”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
“…Similar to ICG-001, PRI-724 inhibits recruitment of beta-catenin to its coactivator, CBP (NCI, 2014). PRI-724 blocks carbon tetrachloride and bile duct ligation induced liver fibrosis in mice (Osawa et al, 2015). C-82 has not been previously administered in any form including topical in humans.…”
Section: Introductionmentioning
confidence: 99%